Pleomorphic adenoma of minor salivary gland of the hard palate. Clinical observations - Kostyshyn, I.; Levandovskyi, R.; Girna, G.; Repetylo, I.; Boyjko, V. (Actual Dentistry, 2018)
Resume. In the article we provide data on prevalence, clinical features, diagnostics and treatment for minor salivary gland pleomorphic adenoma of the hard palate. Also, the initiating step of the orthopedic rehabilitation is discussed. The main diagnostic methods for pleomorphic adenoma of the palate are cytological and histological examination, computed tomography and magnetic resonance imaging. In order to reduce the adenoma relapse probability, we offer a combination therapy: preoperative course of distant gamma-therapy by the intensive program and the operative treatment afterwards. Key words: minor salivary glands, pleomorphic adenoma, relapse, treatment, orthopedic rehabilitation.